Implementation of the Delimitation Contradiction Principle in Land Registration Activities at the South Sorong District Land Office - Dewi Widiyastuti (Journal of Law Justice (JLJ), 2024)
This research aims to find out how the implementation of the Delimitation Contradiction Principle in the process of Land Registration process in the Land Office of South Sorong Regency and to know the legal consequences if the Delimitation Contradiction Principle is not applied in Land Registration. This research was conducted using empirical method by conducting interviews with employees of the Land Office of South Sorong Regency and conducting literature studies, namely books, and conducting literature studies, journals laws, regulations and land documents at the South Sorong District Land Office. The findings obtained from this research include: Principle contradictory delimitation principle is principle in the land registration process, especially at the time of measurement, where the owner of owner of the adjacent land must witness and directly agree on the boundaries of the land parcel to be registered and measured. Disagreement over land parcel boundaries results in the land registration process being hampered. Process becomes obstructed. In addition, every field boundary demarcation must be attended by the landowner and the adjacent landowners. must be attended by the landowner and the adjacent landowners. However, there are times when the party whose land is adjacent cannot be present because they are living outside the city or even abroad.